The role of the agricultural sector in LDCs - Dietrich Kebschull (Intereconomics, 1987)
The growth strategies pursued by the vast majority of developing countries considerably neglect the agricultural sector. The following article discusses the main determinant factors for this discrimination, namely the shortcomings of macroeconomic as well as sectoral and project policies.
Keywords: 330; Agriculture